2014
DOI: 10.1111/bjh.13036
|View full text |Cite
|
Sign up to set email alerts
|

Intensification treatment based on early FDGPET in patients with high‐risk diffuse large B‐cell lymphoma: a phase II GELTAMO trial

Abstract: SummaryWe conducted a multicentre, phase II study of interim positron emission tomography (PET) as a guide to risk-adapted therapy in high-risk patients with newly diagnosed diffuse large B-cell lymphoma (DLBCL). Patients achieving negative fluorodeoxyglucose (FDG)-PET after three courses of RMegaCHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) received three additional courses, whereas PET-positive patients received two courses of R-IFE (rituximab, ifosfamide, etoposide) followed by BE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 41 publications
0
19
1
Order By: Relevance
“…[22][23][24] Notably, these trials showed higher rates of iPET-positivity of 39%, 51%, and 71%, compared to 29% in the present study, meaning that more patients were subject to HDT yet still displayed rates of 2-year PFS (66%, 57%, and 65%) that were no better than those seen in the current study (67%). Other notable differences with these 3 studies were that iPET scans were performed earlier in the treatment course (after 2 or 3 induction cycles), and that the 5-PS was not utilized.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…[22][23][24] Notably, these trials showed higher rates of iPET-positivity of 39%, 51%, and 71%, compared to 29% in the present study, meaning that more patients were subject to HDT yet still displayed rates of 2-year PFS (66%, 57%, and 65%) that were no better than those seen in the current study (67%). Other notable differences with these 3 studies were that iPET scans were performed earlier in the treatment course (after 2 or 3 induction cycles), and that the 5-PS was not utilized.…”
Section: Discussioncontrasting
confidence: 74%
“…Few studies in DLBCL have prospectively explored a change in treatment strategy guided by iPET responses. [22][23][24][25] We chose to evaluate a change to HDT since it is the most widely accepted curative strategy for patients with DLBCL failing R-CHOP. We hypothesized that improved clinical outcomes for high-risk DLBCL patients with poor prognosis as identified by iPET after 4 chemotherapy cycles would be achieved with early HDT and ASCT delivered when there is a lower burden of chemo-resistant disease than if instituted at the time of radiological progression.…”
Section: Introductionmentioning
confidence: 99%
“…CMR on iPET carries an excellent prognosis. Studies evaluating intensification treatment based on iPET have shown no benefit over R-CHOP [69, 70]. Therefore, iPET is not recommended as a basis for altering treatment outside of clinical trials.…”
Section: Response Evaluation and Follow-upmentioning
confidence: 99%
“…In the GELTAMO-2006 [50] clinical trial from Grupo Espanol de Linfomas y Trasplante de Medula Osea (GELTAMO) conducted in 20 Spanish hospitals, 71 patients with untreated, histologically proven DLCBL or grade 3B follicular lymphoma CD20+ that had a baseline PET/CT scan positive with at least one evaluable hyper-metabolic lesion were enrolled. Patients achieving negative PET/CT after three courses of R-MegaCHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) received three additional courses, whereas PET-positive patients received two courses of R-IFE (rituximab, ifosfamide, etoposide) followed by BEAM (BCNU, etoposide, cytarabine, melphalan) and autologous stem-cell transplantation.…”
Section: Strategies Of Error Reduction In Onco-heamatological Clinmentioning
confidence: 99%